2009
DOI: 10.1074/jbc.r900003200
|View full text |Cite
|
Sign up to set email alerts
|

Biological Responses to Arsenic Compounds

Abstract: Arsenic is a metalloid that generates various biological effects on cells and tissues. Depending on the specific tissue exposed and the time and degree of exposure, diverse responses can be observed. In humans, prolonged and/or high dose exposure to arsenic can have a variety of outcomes, including the development of malignancies, severe gastrointestinal toxicities, diabetes, cardiac arrhythmias, and death. On the other hand, one arsenic derivative, arsenic trioxide (As 2 O 3 ), has important antitumor propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
131
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(137 citation statements)
references
References 58 publications
5
131
1
Order By: Relevance
“…50,51 ATO-induced superoxide generation depends on concomitant downregulation of antioxidant enzymes 30,52 and upregulation of oxidases. 32,[53][54][55] The mechanisms through which NPMc þ mediates increased response to bortezomib-or ATO-induced ROS remain to be fully evaluated. NPMc þ expression may disrupt the balance between ROS-generating and ROS-detoxification systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50,51 ATO-induced superoxide generation depends on concomitant downregulation of antioxidant enzymes 30,52 and upregulation of oxidases. 32,[53][54][55] The mechanisms through which NPMc þ mediates increased response to bortezomib-or ATO-induced ROS remain to be fully evaluated. NPMc þ expression may disrupt the balance between ROS-generating and ROS-detoxification systems.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][29] Although the mechanisms underlying ATO-induced cytotoxicity are not completely understood, ATO-mediated induction of ROS has been shown to reduce the membrane potential of mitochondria, enhance the release of cytochrome c and induce both caspasedependent and caspase-independent apoptosis. [30][31][32] AML has a poor prognosis in older patients, and intensive induction carries high morbidity and significant mortality. Thus, new therapies that more specifically target the molecular or metabolic abnormalities within leukemic cells have been highly sought.…”
Section: Introductionmentioning
confidence: 99%
“…15 Arsenic trioxide (AS 2 O 3 ) exhibits potent antileukemic effects in vitro and in vivo and has major clinical activity in the treatment of patients with acute promyelocytic leukemia (APL). [16][17][18] This agent was previously shown to target and eliminate leukemia initiating stem cells (LICs) in mouse models in vivo via PML targeting. 19 Notably, there is evidence that AS 2 O 3 degrades BCR-ABL, 20 raising the possibility that this agent may provide an approach to target CML LICs.…”
Section: Introductionmentioning
confidence: 99%
“…As a meta-estrogen, arsenic promotes mammary carcinogenesis (31). However, arsenic is also a novel promising anticancer agent for treating acute promyelocytic leukemia (APL) 3 and other tumors with mild adverse effects (27)(28)(29)(30). Studies showed that arsenic trioxide produces remissions in patients with APL at least in part through degradation of the aberrant PML-retinoic acid receptor ␣ (PML-RAR␣) fusion protein (32,33).…”
mentioning
confidence: 99%
“…As a known carcinogen, arsenic can induce tumors of the skin, bladder, liver, and lung (27)(28)(29)(30). As a meta-estrogen, arsenic promotes mammary carcinogenesis (31).…”
mentioning
confidence: 99%